Development of a sandwich ELISA for the quantification of enterovirus 71 - Ma, Shujun (Springer Netherlands, 2013)
Since 2008, enterovirus 71 (EV71) has been responsible for high-mortality seasonal epidemics of hand, foot and mouth disease in China. Currently many groups in the world are in the process of developing EV71 vaccines to combat this deadly disease. We have developed three EV71-specific monoclonal antibodies, and in this study we report the establishment of a fast and cost-effective sandwich ELISA kit for measurement of virus concentration in EV71 vaccines using a pair of mouse anti-EV71 monoclonal antibodies. The system is specific for EV71 virus, with no cross-reactivity to coxsackievirus A16, H1N1, rabies, and hepatitis A. Using a reference EV71 vaccine standard, the sensitivity of the assay kit was determined to be 0.82 U/ml, with a linear range between 3.75 and 120 U/ml.